Possibilities of Application of Active Elements in Rolling Stock (Current Problems in Rail Vehicles, 2021)
This article presents examples of the use of active elements in the rolling stock and research results about this topic presented in recent years. The contribution outlines different ways to improve running characteristics of rail vehicles by application actively controlled elements. The authors also reflect on the future development of active elements in rolling stock running gear in connection with current trends in the railway industry.
Keywords: active element; actuator; rolling stock; running gear; active steering